2020
DOI: 10.2196/19417
|View full text |Cite
|
Sign up to set email alerts
|

Application and Preliminary Outcomes of Remote Diagnosis and Treatment During the COVID-19 Outbreak: Retrospective Cohort Study

Abstract: Background The coronavirus disease (COVID-19) pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in the self-quarantine of countless people due to possible infection. This situation makes telemedicine necessary as it can overcome geographical barriers, increase the number of people served, and provide online clinical support for patients. However, the outcomes of telemedicine have not yet b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 18 publications
2
54
0
2
Order By: Relevance
“…Mean age = 60 (SD 15.2) years old; 65% men; 81% were post-op patients. China Questionnaire LOE VI Liu et al. (2020) China Descriptive Retrospective review Adults and Paediatrics Health, and Psychological counselling Jan. 24 to Feb. 17, 2020 4589 patients; 58% females and 42% males; Age range - 78 days old to 85 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean age = 60 (SD 15.2) years old; 65% men; 81% were post-op patients. China Questionnaire LOE VI Liu et al. (2020) China Descriptive Retrospective review Adults and Paediatrics Health, and Psychological counselling Jan. 24 to Feb. 17, 2020 4589 patients; 58% females and 42% males; Age range - 78 days old to 85 years old.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) Earliest remote communication was conducted via Apple FaceTime Institution-licensed platform: Blue Jeans, Doximity LI ET AL. (2020) Video calls using WeChat software LIU ET AL. (2020) In order to consult with a clinician, patients can scan the official QR (Quick Response) code or follow the WeChat public account HNFYSY1904, which directs them to the expert consultation MANN ET AL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some medical centers provide online drug-related services, including placing orders, making payments, and arranging drug prescription and delivery. 13,14 A study of the dietary diversity of China's residents indicates that online services have likely helped residents maintain a diversified diet during pandemic-related confinement. 15 This finding suggests that internet access and online services can help ensure that people continue to receive vitamin D supplements and fortified dietary products during pandemic-related confinement.…”
mentioning
confidence: 99%
“…Various systematic reviews showed a reduction in pain, disability, depression, and anxiety in intervention groups compared to controls (usual care or waitlisted) 21,22 . In addition, it has been observed that virtual outpatient consultations effectively relieved patients' anxiety during the SARS‐CoV‐2 outbreak 23 . Whether a more frequent follow‐up on its own could reduce symptoms and anxiety in patients with pelvic pain is not clear, but it has been reported that a close patient–physician relationship, effective communication, and indeed empathy are valued most highly by patients with chronic pain 24 .…”
Section: Discussionmentioning
confidence: 99%